PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA DENGAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA KELAS IV SEKOLAH DASAR - Susanto, Sofyan (Universitas Nusantara PGRI Kediri, 2017)
The purpose of this research is to develop a learning package for Sciences Subject that can improve the critical thinking skill of the Elementary School Students. Therefore, in general, it can be categorized into a research and development. It can be done because of learning material with process skill to practice it not available. The learning package was developed by using 4-D model; defining, designing, developing, distributing. The subject in this study was learning material that will be tested in student of SDN Karang Tengah 5 Ngawi. The result showed that learning material was valid, enforceability get good category with 100%. Student activites by using process get good too. The improvement of students’ critical thinking is consistent on 2 classes (IVA and IVB), the significant and high improvement with the average of N-Gain of 0,75. Based on the results and findings of the research, it can be concluded that the developed learning package can be stated as a valid, practical, and effective learning package. The implication of the research is that the process skill based Sciences learning can improve students’ critical thinking skill. Keywords : Problem Based Learning, Science, Critical Thinking